2012
DOI: 10.1016/j.neuropsychologia.2012.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Assessing language dominance with functional MRI: The role of control tasks and statistical analysis

Abstract: There is a discrepancy between the brain regions revealed by functional neuroimaging techniques and those brain regions where a loss of function, either by lesion or by electrocortical stimulation, induces language disorders. To differentiate between essential and non-essential language-related processes, we investigated the effects of linguistic control tasks and different analysis methods for functional MRI data. Twelve subjects solved two linguistic generation tasks: (1) a verb generation task and (2) an an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…The Antonym Generation task is reported to provide a higher percentage BOLD signal change in the Broca area (versus baseline) compared with the Antonym Decision task (versus baseline). 41 It is reported that activation of the speech areas and speech lateralization in the various Word Generation tasks (letter, category, antonym word generation) is comparable. 42 However, in our experience with pediatric patients, the Antonym Generation paradigm does much better in terms of the extent of activation in the speech areas and patient compliance versus letter Word Generation tasks; thus, SWG was not included in the pediatric algorithm.…”
Section: Antonym Generation Taskmentioning
confidence: 99%
“…The Antonym Generation task is reported to provide a higher percentage BOLD signal change in the Broca area (versus baseline) compared with the Antonym Decision task (versus baseline). 41 It is reported that activation of the speech areas and speech lateralization in the various Word Generation tasks (letter, category, antonym word generation) is comparable. 42 However, in our experience with pediatric patients, the Antonym Generation paradigm does much better in terms of the extent of activation in the speech areas and patient compliance versus letter Word Generation tasks; thus, SWG was not included in the pediatric algorithm.…”
Section: Antonym Generation Taskmentioning
confidence: 99%
“…Across the papers reviewed here, verbal fluency tasks are consistently reported as yielding the strongest laterality when compared to other receptive and expressive tasks within studies (Baciu et al, 2005;Deblaere et al, 2002;Van der Haegen, Cai & Brysbaert, 2012;Dodoo-Schittko et al, 2012;Harrington, Buonocore & Farias, 2006;Jensen-Kondering et al, 2012;Niskanen et al, 2012;Ocklenburg, Hugdahl & Westerhausen, 2013;Ramsey et al, 2001;Vikingstad et al, 2000;Zaca, Jarso & Pillai, 2013). Studies included in the forest plots produced here report a wide spread of LI values for verbal fluency tasks, ranging from 0.05 to 0.94 (see Fig.…”
Section: Strength Reproducibility and Robustnessmentioning
confidence: 78%
“…region of interest). Interestingly, multiple studies report that LIs from generation tasks can vary substantially depending on methodological choices made when calculating laterality, such as the threshold chosen (Dodoo-Schittko et al, 2012), the use of normalisation, smoothing and clustering techniques (Baciu et al, 2005), and the activity measure used (Harrington, Buonocore & Farias, 2006).…”
Section: Nonsense Text Readingmentioning
confidence: 99%
See 2 more Smart Citations